Thermoelastic model of carpathian region - Бахова, Н.І. (Proceedings of National Aviation University (archive), 2010)
The two-dimensional thermoelastic model of Carpathian region on the basis of a numerical finite elements method is constructed. The physical and mathematical model is as much as possible approached to the real environment. Detailed high-precision distribution of thermoelastic stresses and dislocations is received. The mountainous rocks non-uniform heating and structural non-uniforms leads to considerable changes of stress fields and dislocations in Carpathian region.